Chemical constituents of Pholidota cantonensis. (May 2017) - Li, Bin; Ali, Zulfiqar; Chan, Michael; Li, Juan; Wang, Mei; Abe, Naohito; Wu, Can-Rong; Khan, Ikhlas A.; Wang, Wei; Li, Shun-Xiang
Abstract: Two 9, 10-dihydrophenanthrenes trivially named phocantol and phocantone, two diterpenoid glycosidesnamed phocantoside A and phocantoside B were isolated from the ethanol extract of the air-dried whole plant of Pholidota cantonensis Rolfe, together with seventeen known compounds. The structures of the four compounds were identified as 1-hydroxy-2, 7-dimethoxy-9, 10-dihydrophenanthro-[4, 5- bcd ]furan, 5-hydroxy-2, 7-dimethoxy-9, 10-dihydro-1, 4-phenanthrenedione, (8 R, 13 E )- ent -labd-13-ene-3 α, 8, 15-triol 15- O - β -D-gluco-pyranoside and (5 S, 8 R, 9 S, 10 R )- cis -cleroda-3, 13( E )-diene-15, 18-diol 15- O - β -D-glucopyranosyl-18- O - β -D-glucopyranoside by chemical and spectroscopic methods, including 1D and 2D NMR. Twenty compounds were evaluated for their cytotoxic activities against mouse leukemia p388D1 cancer cells, and compound phocantone, phocantoside A, tanshinone IIA and syringate exhibited cytotoxic activity against the mouse leukemia p388D1 cancer cells with IC50 values ranging from 13.37 to 27.5 μM. Graphical abstract: Four constituents, phocantol, phocantone, phocantoside A, and phocantoside B were isolated from the ethanol extract of the air-dried whole plant of Pholidota cantonensis Rolfe. Highlights: Two diterpenoid glucosides and two dihydrophenanthrenes were isolated from P. cantonensis . These compounds exhibited cytotoxic activity against p388D1 cancer cells. It's rarely that diterpenoid glycosides were isolated from Orchid family.